Role of placental growth factor in neovascularage-related macular degeneration - Rui-Xin Wang (Guoji Yanke Zazhi, 2015)
Choroidal neovascularization is the primary pathogenesis of neovascularage-related macular degeneration(nAMD), and the role of vascular endothelial growth factor(VEGF)in neovascularization has been widely recognized. Currently, drugs target different targets of VEGF have been widely used in the treatment of nAMD. As a subtype of VEGF, placental growth factor(PIGF)has synergistic effects with VEGF-A on promoting angiogenesis, stimulating the migration of endothelial cell proliferation and mediating immune inflammatory response. There is no expression of PIGF in mature blood vessels so PIGF hashigh specificity. In this paper, the role of PIGF in the pathogenesis and treatment of nAMD is reviewed.